2019
DOI: 10.1177/0011000019870308
|View full text |Cite
|
Sign up to set email alerts
|

Measurement and Implications of Perfectionism in South Korea and the United States

Abstract: We evaluated the Short Almost Perfect Scale (SAPS; Rice et al., 2014) in South Korean ( N = 306) and United States ( N = 259) samples. Results supported partial metric invariance for the standards (perfectionistic strivings) and discrepancy (perfectionistic concerns) factors, and for depression and self-esteem. Item responses were unaffected by gender- or age-related bias. Differential item functioning analyses and tests of scalar invariance revealed noninvariance for several items that might reflect culturall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 74 publications
0
5
0
Order By: Relevance
“…On the contrary, self-critical perfectionism may be endorsed and practiced in a relatively favorable way among those strongly oriented to Asian culture and values. Additionally, study findings collectively indicate a distinctive association pattern between perfectionism and mental health indicators between Asian international and Asian American students, presumably due to differing degrees of adherence to Asian cultural values (e.g., Kim & Alamilla, 2017;Rice et al, 2019). Together, studies with a nuanced view of self-critical perfectionism and its impact on mental distress are warranted, with a particular interest in how the degree of one's adherence to the Asian cultural value-operationalized by the group identity-plays a role in the relationship.…”
Section: Perfectionism and Self-cultivation In Asian Culturesmentioning
confidence: 78%
See 1 more Smart Citation
“…On the contrary, self-critical perfectionism may be endorsed and practiced in a relatively favorable way among those strongly oriented to Asian culture and values. Additionally, study findings collectively indicate a distinctive association pattern between perfectionism and mental health indicators between Asian international and Asian American students, presumably due to differing degrees of adherence to Asian cultural values (e.g., Kim & Alamilla, 2017;Rice et al, 2019). Together, studies with a nuanced view of self-critical perfectionism and its impact on mental distress are warranted, with a particular interest in how the degree of one's adherence to the Asian cultural value-operationalized by the group identity-plays a role in the relationship.…”
Section: Perfectionism and Self-cultivation In Asian Culturesmentioning
confidence: 78%
“…Prior research suggests that Asian cultural values and its resulting self-cultivation imperative strongly influence the perception and operation of self-critical perfectionism. For example, in a prior study, components of self-critical perfectionism that extend to the aspirations for self-cultivation were endorsed more highly among Korean students than U.S. students (Rice et al, 2019), potentially because self-cultivation is regarded as virtuous in the traditional Asian culture (Rice et al, 2019; Zane & Song, 2007). Other study findings support this notion, in which among a group of Asian international students, those with high levels of self-critical perfectionism demonstrated better overall adjustment than individuals with low self-critical perfectionism (e.g., Suh et al, 2014), indicating favorable perception and operation of self-critical perfectionism among those with strong ties to Asian culture and its values.…”
Section: Perfectionism and Self-cultivation In Asian Culturesmentioning
confidence: 98%
“…For instance, it is possible that they differ in their level of adherence to Asian cultural values (Suh et al, 2020). Though Asian values were not included in this study, future research is warranted to explore the impact of Asian values in the current research model perhaps in the role of a covariate, given study findings that revealed how the relationship between self-critical perfectionism and mental distress varied according to individuals’ cultural orientation (e.g., Rice et al, 2019). Second, the data collection was limited to those who attended a predominantly White institution located in the southern region of the United States.…”
Section: Discussionmentioning
confidence: 99%
“…Most validity studies of the APS have been completed in convenience samples of university students in psychology classes, which resulted in female-predominant samples. MI results have been mixed by gender, with most studies supporting invariance (Rice et al, 2014;Kira et al, 2018;de Holanda et al, 2021), while a few have indicated at least partial non-invariance at the scalar (intercept) level (Rice et al, 2019). In our population, indeterminate measurement invariance results suggest that any measured mean differences in perfectionism by gender may result from the ways groups perceive perfectionism or reacted to the scale questions, rather than actual differences in the mean levels of perfectionism, and that future work is needed to confirm MI by gender in this population.…”
Section: Discussionmentioning
confidence: 99%